Feasibility study of producing green hydrogen with wind power and its liquefaction : comparing different electrolysis technologies - Anna Lilja Sigurðardóttir 1996- (2022)
Fighting climate change takes on many forms and one of them is going through the green energy transition where fossil fuels are replaced with renewable energy sources such as wind, hydro, solar, or geothermal. The demand for green hydrogen and other electrofuels is expected to rise rapidly over the next years and decades related to the green energy transition and industry. Green hydrogen is a potential fuel for heavy vehicles on land, sea and in air as electrifying some heavy vehicles directly is not considered feasible. Iceland could be the first country to run entirely on green energy as most of Iceland’s electricity is generated from renewable energy sources. However, Iceland imports fossil fuels to supply the transportation sector. Going through the green energy transition not only fights global warming but also increases Iceland’s energy safety, saves the cost of importing fossil fuels, and creates economic value for Iceland. This work is a feasibility study of producing green hydrogen with wind power and its liquefaction for intended hydrogen production in Iceland. Two types of electrolysis technologies suitable to pair with the fluctuating wind energy were compared, polymer electrolyte membrane (PEM) and alkaline mono-polar (AEC). The PEM electrolyser selected is already in use today while the AEC mono-polar electrolyser selected is in the development stage for large-scale use. AEC bi-polar electrolysis plant is connected to the transmission system of Iceland and operated as a baseload. The gaseous hydrogen is liquefied to increase its density. Three questions are presented in this work: Which electrolysis technology is more suitable to connect with the wind farm? Is it possible to utilize all of the energy generated by the wind farm without over-sizing the installed capacity of the electrolysis plant? Is it possible to liquefy the gaseous hydrogen produced with the fluctuating wind energy while operating the liquefaction plant within its optimal range? These questions were answered by creating and ...